Effect on gastric function and symptoms of drinking wine, black tea, or schnapps with a Swiss cheese fondue: randomised controlled crossover trial. (14th December 2010) - Heinrich, Henriette; Goetze, Oliver; Menne, Dieter; Iten, Peter X; Fruehauf, Heiko; Vavricka, Stephan R; Schwizer, Werner; Fried, Michael; Fox, Mark
Abstract : Objective To compare the effects of drinking white wine or black tea with Swiss cheese fondue followed by a shot of cherry schnapps on gastric emptying, appetite, and abdominal symptoms. Design Randomised controlled crossover study. Participants 20 healthy adults (14 men) aged 23-58. Interventions Cheese fondue (3260 kJ, 32% fat) labelled with 150 mg sodium 13 Carbon-octanoate was consumed with 300 ml of white wine (13%, 40 g alcohol) or black tea in randomised order, followed by 20 ml schnapps (40%, 8 g alcohol) or water in randomised order. Main outcome measures Cumulative percentage dose of 13 C substrate recovered over four hours (higher values indicate faster gastric emptying) and appetite and dyspeptic symptoms (visual analogue scales). Results Gastric emptying was significantly faster when fondue was consumed with tea or water than with wine or schnapps (cumulative percentage dose of 13 C recovered 18.1%, 95% confidence interval 15.2% to 20.9% v 7.4%, 4.6% to 10.3%; P<0.001). An inverse dose-response relation between alcohol intake and gastric emptying was evident. Appetite was similar with consumption of wine or tea (difference 0.11, −0.12 to 0.34; P=0.35), but reduced if both wine and schnapps were consumed (difference −0.40, −0.01 to −0.79; P<0.046). No difference in dyspeptic symptoms was present. Conclusions Gastric emptying after a Swiss cheese fondue is noticeably slower and appetite suppressed if consumed with higher doses of alcohol. This effect was not associated with dyspeptic symptoms. Trial registration ClinicalTrials.gov NCT00943696 .